The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1109/ted.2017.2669645
|View full text |Cite
|
Sign up to set email alerts
|

The Avalanche-Mode Superjunction LED

Abstract: Abstract-Avalanche-mode light-emitting diodes (AMLEDs) in silicon (Si) are potential light sources to enable monolithic optical links in standard CMOS technology, due to the large overlap of their electro-luminescent (EL) spectra with the responsivity of Si photo-diodes. These EL spectra depend on the reverse electric field. We present, for the first time, AMLEDs employing the superjunction (SJ) assisted reduced surface field (RESURF) effect which increases the uniformity of their electric field profile. Conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
0
10
1
1
Order By: Relevance
“…Further work by Xu et al led to the realization of a series of CMOS integrated LED devices with third terminal gated control [8]. Subsequently, the temperature, carrier density, and electric field encountered in Silicon Avalanche Mode Light Emitting Devices (Si AMLEDs) were analyzed by Duttal and Steeneken et al They also suggested operation of gated Si LED operating in the forward-biased mode and emitting in the 1100 nm region [12]. A major advantage with these devices is the realization of high modulation speeds ranging into the GHz due to the reverse bias configuration of Si AMLEDs [25,26].…”
Section: Light Emitting Characteristics From Silicon Amledsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work by Xu et al led to the realization of a series of CMOS integrated LED devices with third terminal gated control [8]. Subsequently, the temperature, carrier density, and electric field encountered in Silicon Avalanche Mode Light Emitting Devices (Si AMLEDs) were analyzed by Duttal and Steeneken et al They also suggested operation of gated Si LED operating in the forward-biased mode and emitting in the 1100 nm region [12]. A major advantage with these devices is the realization of high modulation speeds ranging into the GHz due to the reverse bias configuration of Si AMLEDs [25,26].…”
Section: Light Emitting Characteristics From Silicon Amledsmentioning
confidence: 99%
“…If the detailed dispersion characteristics observed per solid angle for a particular device is known, it can enable the design of novel and futuristic on-chip electro-optic applications. Examples of such applications could include wavelength multiplexers for on-chip communication, diverse futuristic on-chip micro-and nano-dimensioned gas sensors and even on-chip biosensors [11][12][13][14]. In this chapter, a two-junction micro-dimension p + −np + Silicon Avalanche-based Light Emitting Device (Av Si LED) has been analyzed in terms of radiation geometrical dispersion characteristics, and with particular interest in the different wavelengths of light (colors) being emitted at different emission angles from the surface of the device.…”
Section: Introductionmentioning
confidence: 99%
“…• The superjunction light-emitting diode (SJLED) [14], [15]. In this work we focus on the last approach.…”
Section: Introductionmentioning
confidence: 99%
“…The grey dashed line represents results obtained from Fulop's approximation [30], showing a discrepancy for smaller L. at breakdown (E x (x)) in the drift (or "active") region of the p-i-n diode, see Fig. 1(c), results in a higher EL-intensity thus η RAD compared to conventional pn junctions with the same breakdown voltage (BV ) [14]. In the latter E x (x) is triangularly shaped and hence only near the peak field, light emission spots will form.…”
Section: Introductionmentioning
confidence: 99%
“…Исследователи из Нидерландов предложили конструкцию оптопары на основе кремниевых лавинных светодиодов [19]. Ими достигнута эффективность оптоэлектронной передачи сигнала (коэффициент передачи по току) 10 -8 .…”
Section: Introductionunclassified